(untitled) (Encuentros, 2016)
This article exposes the result of a research process developed in a University from the Colombian Caribbean, which had the purpose of making an analysis of the intercultural competences of higher education students in online learning courses. This is a quantitative, descriptive and exploratory research, based on survey. For this study, there were selected a group of 68 students that were attending online learning courses in a higher education institution, these students answered a survey through an online form. The results show us that a high percent of students consider themselves proficient in the two sub-competences defined as: efficacy between diverse cultures and, development of the understanding and respect of differences and diversity. Keywords: Interculturality, Virtual Environments, higher education, intercultural competence, diversity, culture